2019
DOI: 10.1056/nejmoa1811850
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Four Treatment Approaches for Actinic Keratosis

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
175
3
16

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(199 citation statements)
references
References 21 publications
5
175
3
16
Order By: Relevance
“…PDT for AKs has excellent if not superior outcomes when compared to other treatments, and recent studies suggest that PDT with 5‐FU pretreatment produces synergistic effects . Most recently, a randomized trial comparing 5‐FU, 5% imiquimod, MAL‐PDT, and ingenol mebutate found the cumulative probability of remaining disease free at 12 months in the group treated with 5‐FU (74.7%; 95% CI 66.8‐81.0), with 5% imiquimod (53.9%; 95% CI 45.4‐61.6), MAL‐PDT (37.7%; 95% CI 30.0‐45.3), and ingenol mebutate (28.9%; 95% CI 21.8‐36.3)), and the hazard ratio of treatment failure with MAL‐PDT compared to 5‐FU was 2.73 (95% CI 1.87‐3.99) …”
Section: Efficacy For Solid Tumorsmentioning
confidence: 99%
“…PDT for AKs has excellent if not superior outcomes when compared to other treatments, and recent studies suggest that PDT with 5‐FU pretreatment produces synergistic effects . Most recently, a randomized trial comparing 5‐FU, 5% imiquimod, MAL‐PDT, and ingenol mebutate found the cumulative probability of remaining disease free at 12 months in the group treated with 5‐FU (74.7%; 95% CI 66.8‐81.0), with 5% imiquimod (53.9%; 95% CI 45.4‐61.6), MAL‐PDT (37.7%; 95% CI 30.0‐45.3), and ingenol mebutate (28.9%; 95% CI 21.8‐36.3)), and the hazard ratio of treatment failure with MAL‐PDT compared to 5‐FU was 2.73 (95% CI 1.87‐3.99) …”
Section: Efficacy For Solid Tumorsmentioning
confidence: 99%
“…A recently published clinical trial showed that topical 5% fluorouracil (5-FU) was significantly more effective than imiquimod, methyl aminolevulinate-PDT (MAL-PDT) or ingenol mebutate at 12 months after the end of treatment for multiple AK lesions [16]. Similar findings were shown in a network meta-analysis [17].…”
Section: -Fluorouracilmentioning
confidence: 63%
“…This is a head‐to‐head evaluation of four common AK field treatments . Rather than an outcome immediately post‐treatment, this trial's primary outcome was longer term: AK reduction at 12 months.…”
Section: Commentmentioning
confidence: 99%